2019
DOI: 10.4102/phcfm.v11i1.1819
|View full text |Cite
|
Sign up to set email alerts
|

Low back pain among primary school teachers in Rural Kenya: Prevalence and contributing factors

Abstract: Background: Low back pain (LBP) has been recognised as a common occupational problem with a high prevalence among work-related musculoskeletal disorders. Although there appears to be a high prevalence of LBP among school teachers, there is inadequate information on the prevalence and predisposing factors of LBP among primary school teachers in rural Western Kenya.Aim: To determine the prevalence, factors associated with LBP and physical disability caused by LBP.Setting: The setting was public schools in rural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
33
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 24 publications
6
33
1
7
Order By: Relevance
“…The significant drop of prevalence of MSDs with age as well as with job seniority can be due to the fact that older teachers usually have more responsibilities which demand less physical efforts than younger ones. A couple of study showed that younger workers face greater work demands, being exposed to risk factors, as they take over more activities and tasks in the beginning of the career [15,20]. Other researchers found similar results to our study [1,8,10,17].…”
Section: Discussionsupporting
confidence: 88%
“…The significant drop of prevalence of MSDs with age as well as with job seniority can be due to the fact that older teachers usually have more responsibilities which demand less physical efforts than younger ones. A couple of study showed that younger workers face greater work demands, being exposed to risk factors, as they take over more activities and tasks in the beginning of the career [15,20]. Other researchers found similar results to our study [1,8,10,17].…”
Section: Discussionsupporting
confidence: 88%
“…This was higher than the rates reported by teachers in China with 48.7% in the neck and 45.6% in the neck/shoulders (23); Turkey with 43.8% in the lower back, 42.5% in the neck, and 43.8% in the shoulders (45); and Brazil with 49.6% in the lower back and 50.2% in the neck (19). These results place Chilean urban teachers among those with the highest MSD prevalence in these body segments, similar to teachers in Nigeria with 62.3% in the shoulders and 57.9% in the neck (12); Saudi Arabia with 63.8% in the lower back, 45.4% in the shoulders, and 42.1% in the neck (16); or Kenya with 64.98% in the lower back (21). It should be considered that in this study all urban teachers did classes in primary and/or secondary schools.…”
Section: Discussionsupporting
confidence: 55%
“…Furthermore, a close relation exists between MSD and classroom experience years, age range, female gender (12), obesity (13)(14)(15), school type and number of students assigned (16), school infrastructure, work conditions, high stress, and psychosocial factors (4,10,(17)(18)(19), with links even being observed with the urban or rural area where teachers work (20). MSDs have been studied in both developed and developing countries, with high prevalence in body segments including the lower back, neck, shoulders, and upper limbs (14,(21)(22)(23). In this way, evidence exists regarding the relation between MSD and quality of life (QoL) perception in teachers (10,11,24).…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, back pain is one of the most common musculoskeletal disorders, ranking among the top 10 most frequent health issues [10]. The point prevalence of lower back pain in teachers is reported as follows: 21.8% [11], 38.1% [12], 40.4% [4], 45.6% [13], 64.98% [14], and 74.8% [15], and the point prevalence of cervical spine pain has been reported as: 11.3% [12], 24% [16], 48.7% [13], and 69.3% [17]. Wáng et al, (2016) reported higher back pain prevalence in females than in males, especially after menopausal age, in their systematic review [18].…”
Section: Introductionmentioning
confidence: 99%